Adoption of mechanical seeder among rice farmers in Cagayan Valley Region, Philippines - Badua, Aldrin E; Vargas, Danilo S; Baltazar, Eugenia G; Aveno, Jocelyn L; Orden, Maria Excelsis M. (Asian Journal of Agriculture and Rural Development, 2024)
This study examines the adoption of mechanical seeder among rice farmers in Cagayan Valley Region, Phillippines. Mechanical seeder is a machine for planting rice. The mechanical seeder was initially introduced to rice farmers in the Cagayan Valley Region, Philippines. This study assessed the adoption factors regarding farmers' acceptance and utilization of the mechanical seeder. The respondents in this study were the farmer-users of the mechanical seeder for rice. All data were gathered through the use of an interview schedule. Data were analyzed using correlations, linear, and logistic regression. Results revealed that hearing/reading as an independent variable showed a significant correlation with technology acceptance and a highly significant correlation with attendance at promotional activities and training. A farmer who attended the promotional activities has a greater probability of accepting the technology. Attending promotional activities like lecture discussions, demonstrations, field days, seminars, and exhibitions by the farmer-users facilitated the acceptance of mechanical seeder technology. Attendance at promotional activities was also a significant predictor of a higher level of acceptance of the mechanical seeder among farmer users (p<0.01), and the size of the farm was a significant predictor of a higher level of utilization among farmer users (p<0.01). The different mechanical seeder attributes like ease of use, usefulness, and relative advantage positively affected farmer respondents' acceptance and utilization levels.